Comprehensive assessment for autonomic dysfunction in different phases after ischemic stroke. Issue 8 (3rd July 2012) - Xiong, Li; Leung, Howan H. W.; Chen, Xiang Yan; Han, Jing Hao; Leung, Thomas W. H.; Soo, Yannie O. Y.; Chan, Anne Y. Y.; Lau, Alexander Y. L.; Wong, Lawrence K. S.
<x xml:space="preserve">Abstract</x> Background and purpose Studies mostly use the analysis of heart rate variability to measure cardiovascular autonomic regulation in ischemic stroke. Besides power spectral analysis of heart rate variability, this study sought to determine whether autonomic function was impaired during different phases in ischemic stroke by Ewing's battery of autonomic function tests. Methods Ninety‐four patients with ischemic stroke (34 patients in acute phase and 60 patients in chronic phase, average six‐months after stroke onset) and thirty‐seven elderly controls were recruited. Ewing's battery autonomic function tests and power spectral analysis of heart rate variability were performed in all the subjects. Results From power spectral analysis of heart rate variability, stroke patients of both acute and chronic phases had significantly lower low frequency power spectral density than controls. From Ewing's battery of autonomic function tests, patients in acute phase showed impairment in two parasympathetic tests (Valsalva ratio: P = 0·002; heart rate response to deep breathing: P < 0·001) and those in chronic phase showed impairment in all parasympathetic tests (all P < 0·05) in comparison with controls. Conclusions The comprehensive assessment indicates that autonomic dysfunction occurs in acute phase of ischemic stroke and may persist up to six‐months after stroke. Parasympathetic dysfunction rather than sympathetic dysfunction is predominant after ischemic stroke.